Evaluation of SINERGIAPS, an intervention to improve patient safety in primary healthcare centers in Spain based on patients’ perceptions and experiences: a protocol for a hybrid type I randomized clinical trial - Maria A. Fiol-deRoque; Maria A. Fiol-deRoque; Georgina Vidal Mansilla; José A. Maderuelo-Fernández; José A. Maderuelo-Fernández; José A. Maderuelo-Fernández; Olaya Tamayo-Morales; Olaya Tamayo-Morales; Francisco Martín-Luján; Pilar Astier-Peña; Pilar Astier-Peña; Macarena Chacón-Docampo; et al. (Frontiers in Public Health, 2024)
BackgroundAdverse events in the primary care setting result in a direct cost equivalent to at least 2.5% of total healthcare spending. Across OECD countries, they lead to more than seven million avoidable hospital admissions annually. In this manuscript, we describe the protocol of a trial aimed at evaluating the effectiveness of SinergiAPS (a patient-centered audit and feedback intervention) in reducing avoidable hospital admission and explore the factors that may affect its implementation.MethodsWe will conduct a 24-month, parallel, open-label, multicenter, pragmatic, hybrid type 1 randomized clinical trial. 118 primary healthcare centers with wide geographical distribution in Spain will be randomly assigned (ratio 1:1) to two groups. The intervention group will receive two audits (baseline and intermediate at 12 months) based on information collected through the administration of the PREOS-PC questionnaire (a measure of patient-reported patient safety) to a convenience sample of 100 patients per center. The intervention group will receive reports on the results of both audits, along with educational resources aimed at facilitating the design and implementation of safety improvement plans. The control group will receive care as usual. The primary outcome will be the rate of avoidable hospitalizations (administrative data). Secondary outcomes: patient-reported patient safety experiences and outcomes (PREOS-PC questionnaire); patient safety culture as perceived by professionals (MOSPSC questionnaire); adverse events reported by healthcare professionals (ad hoc questionnaire); the number of safety improvement actions which the re has implemented (ad hoc questionnaire). Outcome data will be collected at baseline and 24 months follow-up. For the evaluation of the implementation of the SinergiAPS intervention, we will draw on the Consolidated Framework for Implementation Research (CFIR). We will collect and analyze qualitative and quantitative data (30 individual interviews, implementation logbooks; questionnaires for professionals from intervention centers, and level of use of the SinergiAPS web tool).DiscussionThis study will expand the scarce body of evidence existing regarding the effects and implementation of interventions aimed at promoting patient and family engagement in primary healthcare, specifically for enhancing patient safety. The study has the potential to produce an impact on clinical practice, healthcare systems, and population health.Clinical Trial Registration: https://clinicaltrials.gov/study/NCT05958108?term=sinergiAPS&rank=1 (NCT05958108).